Chymase-mediated intestinal epithelial permeability is regulated by a protease-activating receptor/matrix metalloproteinase-2-dependent mechanism - Groschwitz, Katherine R. (American Physiological Society, 2013)
Mast cells regulate intestinal barrier function during disease and homeostasis. Secretion of the mast cell-specific serine protease chymase regulates homeostasis. In the present study, we employ in vitro model systems to delineate the molecular pathways involved in chymase-mediated intestinal epithelial barrier dysfunction. Chymase stimulation of intestinal epithelial (Caco-2 BBe) cell monolayers induced a significant reduction in transepithelial resistance, indicating decreased intestinal epithelial barrier function. The chymase-induced intestinal epithelial barrier dysfunction was characterized by chymase-induced protease-activated receptor (PAR)-2 activation and matrix metalloproteinase (MMP)-2 expression and activation. Consistent with this observation, in vitro analysis revealed chymase-induced PAR-2 activation and increased MAPK activity and MMP-2 expression. Pharmacological and small interfering RNA-mediated antagonism of PAR-2 and MMP-2 significantly attenuated chymase-stimulated barrier dysfunction. Additionally, the chymase/MMP-2-mediated intestinal epithelial dysfunction was associated with a significant reduction in the tight junction protein claudin-5, which was partially restored by MMP-2 inhibition. Finally, incubation of Caco-2 BBe cells with chymase-sufficient, but not chymase-deficient, bone marrow-derived mast cells decreased barrier function, which was attenuated by the chymase inhibitor chymostatin. Collectively, these results suggest that mast cell/chymase-mediated intestinal epithelial barrier function is mediated by PAR-2/MMP-2-dependent pathways.